Electronic prescribing and medication management at a residential aged care facility - Elliott, Rohan A.; Lee, Cik Yin; Hussainy, Safeera Y. (Applied Clinical Informatics, 2016)
A cloud-based mobile electronic prescribing and medication management system (ePMMS), in which prescribers’ orders directly populate residential aged care facility (RACF) medication administration records (MARs) and are communicated electronically to the RACF’s pharmacy, may create efficiencies and improve patient safety when compared to the paper-based and hybrid paper-electronic medication management systems used in most Australian RACFs. Little is known about general-practitioners’ (GPs’), nurses’ and pharmacists’ acceptance of, or experiences with, ePMMS.To explore the uptake of an ePMMS by GPs, and the experiences and perceptions of GPs, nurses and pharmacists, at a 90-bed RACF that tested a beta-version ePMMS.Retrospective audit to determine the proportion of medicines ordered by GPs via the ePMMS over a three-month period. Focus groups conducted three-to-four months after implementation: one with GPs (n=5), one with nurses (n=12); in-depth interview/survey of pharmacists (n=2). Qualitative data were analysed thematically.Three of seven GPs used the ePMMS to order medicines; 53/205(25.9%) medicines were ordered via the ePMMS by GPs.Two broad themes were identified: benefits of the ePMMS, and barriers/limitations. Benefits related to patient safety and workforce efficiency, and included GPs’ ability to access and modify residents’ MARs remotely, no need for nurses to fax orders to the pharmacy, and no need for pharmacy transcription of GPs’ handwritten orders to create electronic MARs. Barriers and limitations related to inefficiency, low GP uptake and training/support, and included slower prescribing compared to written orders, the need for GP-signed paper copies of the MAR, lack of integration with GP clinic software, and low GP motivation to use the system, especially GPs with few patients at the RACF.GPs, nurses and pharmacists felt the ePMMS improved medication-safety and workforce-efficiency, however a number of barriers were identified that contributed to low GP-uptake and limited the benefits.
Keywords: Electronic prescribing; residential facilities; general practitioners; Australia